A dyslexic-type profile, anxiety and school-related stress in primary aged students : a New Zealand study : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Educational Psychology at Massey University, New Zealand - Smith, Heather May (Massey University, 2019)
The acknowledgement and identification of dyslexia are long overdue in New Zealand’s education system, and there is currently little understanding of the prevalence or emotional correlates of dyslexia in Aotearoa. Research offers a range of prevalence rates (3-20%), based on various operationalised definitions. The literature also suggests that a variety of emotional difficulties often co-exist with dyslexia, yet aspects of anxiety specific to research on primary school-aged groups are underrepresented in the literature. This study had two aims. First, this study aimed to identify the prevalence of a dyslexic- type profile (D-TP) in New Zealand for 8-10-year-old students. Secondly, this study explored the difference in anxiety and school-related stress experienced by students with a D-TP, when compared to generic poor readers and students with no significant reading difficulty. It was hypothesised that students with a D-TP will report significantly more anxiety and school-related stress than their peers. A quantitative approach, using Nicholson and Dymock’s (2015) SVR operationalised definition of dyslexia was employed with 54, 8 to 10-year-old students attending six different primary schools in the South Island of New Zealand, to establish a prevalence figure for a D-TP. Two standardised questionnaires (Spence Children’s Anxiety Scale and the School Situational Survey) were administered to all participants, to gauge group differences in anxiety, across six dimensions, and school-related stress, across seven dimensions. The results indicated an 11% prevalence rate for a D-TP, based on the SVR criteria: a figure that appears elevated in comparison to other countries; may only represent moderate to severe dyslexia, and is likely an underestimate of the prevalence of a D-TP. Questionnaire response analyses showed that the D-TP group reported significantly greater anxiety and school-related stress than their peer groups. The study contributes towards an understanding of how the SVR-based methodology may be utilised in New Zealand for 8 to10-year-olds as an assessment for the identification of a dyslexic-type profile. It is also concluded that students with a D-TP experience greater anxiety and school-related stress than poor readers and proficient readers: a feature that not only distinguishes this group but calls for awareness in relation to their well-being.
Keywords: Dyslexia; New Zealand; Dyslexic children; Education (Elementary); Mental health; Reading comprehension; Ability testing; dyslexia; dyslexic-type profile; Simple View of Reading; anxiety; school-related stress; 520102 Educational psychology